Adaptive Architecture for Secure Digital Payments - Swapnil Baradhwaj Kadiyam (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The expansion of digital payment technologies has ushered in transformative benefits for global commerce but has also introduced complex security, usability, and regulatory challenges. This research builds upon existing security frameworks by addressing significant gaps in real-world implementation, inclusive design, quantum readiness, and policy adaptation. Through a multi-dimensional analysis, the study investigates the disconnect between theoretical frameworks and production-scale deployments, especially in diverse market environments with infrastructure constraints. It emphasizes the importance of human-centered design in authentication systems, explores insider threat mitigation strategies, and introduces proactive security models including role-based controls and Zero Trust Architecture. Finally, the paper offers actionable strategies for scaling secure digital payment infrastructures while maintaining usability, compliance, and future-proofing against emerging technological risks. The findings aim to guide software developers, financial institutions, and policymakers in building resilient, inclusive, and regulation-aware payment systems for the next decade.
Keywords: Smart Payment Security; Inclusive Digital Finance; Insider Threat Mitigation; Multi-Factor Authentication; Post-Quantum Cryptography; Zero Trust Architecture; Usability and Accessibility in FinTech